PENERAPAN CONTEXTUAL TEACHING AND LEARNING (CTL) BERBANTUAN E-MODUL INTERAKTIF DALAM MENINGKATKAN LITERASI SAINS PADA MATERI BUMIKU SAYANG BUMIKU MALANG DI KELAS V SD NEGERI 1 SUMBANG : PENELITIAN TINDAKAN KELAS - Amanda Syahidah Al; Badarudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The low science literacy of students at SD Negeri 1 Sumbang, especially in understanding the IPAS material “Bumiku Sayang Bumiku Malang”, is the problem identified in this study. The lack of contextual teaching materials and the use of conventional learning methods cause students' interest and critical thinking skills to decline. This study aims to improve students' science literacy through the application of Contextual Teaching and Learning (CTL) learning model assisted by interactive e-modules. This study used the Classroom Action Research (PTK) method of the Kemmis and McTaggart model, carried out in two cycles, each consisting of two meetings. Data collection instruments included teacher and student activity observations, and science literacy tests. The results showed that the application of CTL model assisted by interactive e-module effectively improved students' science literacy. This is indicated by an increase in the percentage of student learning completeness on IPAS material, as well as an increase in student learning activities in the classroom. Thus, the use of the CTL model assisted by interactive e-modules can be an innovative alternative in improving science literacy skills in elementary schools.